What Mothers Know about Newborn Bloodspot Screening and the Sources They Use to Acquire This Knowledge: A Pilot Study in Flanders - Caroline di Gangi; Maren Hermans; Maissa Rayyan; François Eyskens; Karel Allegaert (MDPI AG, 2023)
To learn what mothers know about newborn bloodspot screening (NBS), the procedure, and the sources used, a pilot study was performed. An online questionnaire was developed, with the first part focused on characteristics and the NBS procedure, and the second on knowledge, information sources, and health care providers (HCPs). This questionnaire was accessible until 200 answers were received. The characteristics of respondents were representative for the population. Mothers gave verbal consent in 69.5% of cases, 12.5% did not, and 18% stated that no consent was requested. The 'knowledge' part contained 12 closed questions, five multiple-choice questions on sources, and assessments (5-point Likert scores) of the information transfer. The mean knowledge level was 7.2/12. Screening concepts (consequences, likelihood, sensitivity, carrier) and absence of notification of normal findings were well known. The fact that NBS is not compulsory was poorly known, and post-analysis sample handling procedures were poorly understood. Key HCPs were midwifes (80.5%) and nurses (38.5%). When the leaflet (44%) was provided, the majority read it. Mean Likert scores were 3.36, 3.38, 3.11 and 3.35 for clarity, timing appropriateness, sufficiency, and usefulness. The knowledge level and consent practices were reasonably good. Key HCP were midwives and nurses, the leaflets were supporting. This should enable a quality improvement program to a sustainable NBS program in Flanders.